“Sensing” The Destination: Assessing Multisensory Experiences in Outdoor Tourism - Ratna Roostika; Rizqi Adhyka Kusumawati; Titik Kuntari; Punik Mumpuni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to understand the impact of multisensory experiences on place attachment, visitors' involvement, and revisit intention of outdoor tourism locations. A quantitative approach was chosen by distributing questionnaires to visitors of outdoor destinations in Yogyakarta and surrounding areas. The PLS-SEM technique was used to statistically analyze data from 418 valid respondents. The results showed that multisensory experiences positively influenced place attachment, visitor involvement, and intention to revisit. In addition, place attachment and visitor involvement were also found to have an impact on revisit intentions. By visiting outdoor destinations such as parks, gardens, mountains, temples, and beaches, visitors expect to find a state of relaxation and happiness, as all five senses receive stimulation from pleasant environments. This study complements previous research and broadens the scope of marketing and tourism research by analyzing multisensory experience variables so that destinations can play a greater role in people's mental health. This study also offers valuable new alternatives for the development of tourism marketing and tourism structuring strategies in the future, especially promoting tourism that cares about mental health.